2018
DOI: 10.1177/1535370218816653
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine regulation of lung disease and inflammation

Abstract: Sex-based disparities have been identified in respiratory physiology, and in many chronic lung diseases including asthma, chronic obstructive pulmonary disease, and cystic fibrosis. The observed sex differences in lung disease prevalence and incidence have been linked to changes in circulating levels of sex hormones that start after puberty and that have been shown to affect physiological and immunological functions. While the exact roles of male and female sex hormones in these processes have not been fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 126 publications
1
57
0
1
Order By: Relevance
“…Inhaled nano‐carbons and cSiO 2 are reported to cause greater lung inflammation in female animals, but present greater carcinogenic and fibrotic potential in males (Brass et al, ; Kasai et al, ; Latoche et al, ). These results are similar to human reports of worse inflammatory lung disease in women and fibrosis and cancer in men (Fuentes & Silveyra, ; Pinkerton et al, ). Many of the studies in this review focus on the lungs as the primary target organ in inhalation exposures, however, it has been reported that NPs are able to translocate from the lungs to organs such as the brain, lymph nodes, liver, and kidneys (Mercer et al, ), and also have the ability to alter systemic immune function following inhalation exposure (Mitchell et al, ; Mitchell, Lauer, Burchiel, & McDonald, ; Smith, Brown, Zamboni, & Walker, ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Inhaled nano‐carbons and cSiO 2 are reported to cause greater lung inflammation in female animals, but present greater carcinogenic and fibrotic potential in males (Brass et al, ; Kasai et al, ; Latoche et al, ). These results are similar to human reports of worse inflammatory lung disease in women and fibrosis and cancer in men (Fuentes & Silveyra, ; Pinkerton et al, ). Many of the studies in this review focus on the lungs as the primary target organ in inhalation exposures, however, it has been reported that NPs are able to translocate from the lungs to organs such as the brain, lymph nodes, liver, and kidneys (Mercer et al, ), and also have the ability to alter systemic immune function following inhalation exposure (Mitchell et al, ; Mitchell, Lauer, Burchiel, & McDonald, ; Smith, Brown, Zamboni, & Walker, ).…”
Section: Resultssupporting
confidence: 91%
“…Often, lung pathology resulting from inhaled particles is not due to the pathogenic effects of the particles themselves, but rather the immune‐mediated inflammatory response (Jacobs & Kligerman, ). Clinical, epidemiological, and experimental data have demonstrated the importance of sex‐steroid hormone signaling on immune‐regulation in respiratory disease settings (Carey, Card, Voltz, Germolec, ; Fuentes & Silveyra, ; González‐Arenas & Agramonte‐Hevia, ; Sathish, Martin, & Prakash, ; Tam et al, ). Sex‐steroid hormone receptors are expressed by a variety of immune cell types including macrophages, dendritic cells, granulocytes (mast cells in particular), and lymphocytes (Buskiewicz, Huber, & Fairweather, ; Zierau, Zenclussen, & Jensen, ).…”
Section: Sex‐differences In the Respiratory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…). In addition, lung cells also express sex hormone receptors, including estrogen and progesterone nuclear and membrane receptors, known to mediate several functions of the organ, and specifically immune responses (Fuentes and Silveyra ). Some studies, including ours, have hypothesized that female sex hormones can act as functional regulators of lung function and immunity through regulation of inflammatory gene expression (Card and Zeldin ; Tam et al.…”
Section: Discussionmentioning
confidence: 99%
“…Female sex hormones are putative mediators of respiratory health, and regulate bronchodilation, cell proliferation, inflammation and metabolism of toxic cigarette smoke-related metabolites 1 4–7. Notably, oestrogen and progesterone appear to have varying effects on lung function across the lifespan 1.…”
Section: Introductionmentioning
confidence: 99%